Respiratory syncytial virus-associated seizures in Korean children, 2011-2016 - Teahyen Cha; Young Jin Choi; Jae-Won Oh; Chang-Ryul Kim; Dong Woo Park; In Joon Seol; Jin-Hwa Moon (Korean Pediatric Society, 2019)
Purpose Respiratory syncytial virus (RSV) infection can cause various neurological complications. This study aimed to investigate the RSV-associated neurologic manifestations that present with seizures. Methods We retrospectively reviewed the medical records of patients aged less than 15 years with laboratory-confirmed RSV infections and seizures between January 2011 and December 2016 in a regional hospital in South Korea. Results During this period, 1,193 patients with laboratory-confirmed RSV infection were identified. Of these, 35 (35 of 1,193, 2.93%; boys, 19; girls, 16; mean age: 20.8±16.6 months) presented with seizures. Febrile seizure was the most common diagnosis (27 of 35, 77.1%); simple febrile seizures in 13 patients (13 of 27, 48.1%) and complex febrile seizures in 14 (14 of 27, 51.9%). Afebrile seizures without meningitis or encephalopathy were observed in 5 patients (5 of 35, 14.3%), seizures with meningitis in 2 (2 of 35, 5.7%), and seizure with encephalopathy in 1 (1 of 35, 2.9%) patient. Lower respiratory symptoms were not observed in 8 patients. In a patient with encephalopathy, brain diffusion-weighted magnetic resonance imaging revealed transient changes in white matter, suggesting cytotoxic edema as the mechanism underlying encephalopathy. Most patients recovered with general management, and progression to epilepsy was noted in only 1 patient. Conclusion Although febrile seizure are the most common type of seizure associated with RSV infection, the proportion of patients with complex febrile seizures was higher than that of those with general febrile seizures. Transient cytotoxic edema may be a pathogenic mechanism in RSV-related encephalopathy with seizures.